การพัฒนารูปแบบการให้ข้อมูลย้อนกลับโดยเพื่อนเพื่อเสริมสร้างทักษะการเขียนภาษาไทยของผู้เรียนที่ใช้ภาษาไทยเป็นภาษาที่สอง - ฟาสีฮะห์ อาแว (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This research and development aimed to: 1) develop the peer feedback model to enhance Thai writing skill of Thai as a second language learners 2) compare Thai writing development of learners between those who used peer feedback model and did not 3) compare Thai writing development of students who have high, medium and low Thai writing performance when they received feedback from peer who had different level skill and 4) to evaluate effectiveness of using peer feedback model. Participants were 254 eleventh grade students in Pattani. The data were collected through the peer feedback model manual, evaluation form, and attitude scale and interview schedule. The quantitative data were analyzed by descriptive statistic, two-way mixed ANOVA, t-test and one-way ANOVA. The qualitative data were analyzed by content analysis. The research findings were as follows: 1) the peer feedback model to enhance Thai writing skill of Thai as a second language learners consisted of four components, including the principle of the model, the goal of the model, teaching and learning activities, and peer feedback form 2) Overall Thai writing development of students who used peer feedback model were higher than students who did not at 0.1 level significant 3) Thai writing development of students who had high level, medium level and low level of Thai writing performance was not significantly different when they received feedback from peers who had different skill and 4) the effectiveness of the peer feedback model revealed the student who had the development in Thai writing performance meant they had higher post-test than pretest at 0.1 level significant, the students had positive attitude towards the peer feedback model. In addition, teacher and student were accepting the possibility of the practical.